Manipulating theophany : light and ritual in north Adriatic architecture (ca. 400-ca. 800) - Ivanovici, Vladimir (Boston : De Gruyter, 2016)
Using light as fil rouge reuniting theology and ritual with the architecture, decoration, and iconography of cultic spaces, the present study argues that the mise-en-scène of fifth-century baptism and sixth-century episcopal liturgy was meant to reproduce the luminous atmosphere of heaven. Analysing the material culture of the two sacraments against common ritual expectations and Christian theology, we evince the mannerin which the luminous effect was reached through a combination of constructive techniques and perceptual manipulation. One nocturnal and one diurnal, the two ceremonials represented different scenarios, testifying to the capacity of church builders and willingness of Late Antique bishops to stage the ritual experience in order to offer God to the senses.
Introduction -- Paulinus of Nola and the new visual rhetoric of sanctity -- Light in late antique baptismal theory and practice -- Initiation and light theophanies in late antiquity -- Christian bishops on reflecting the image of God at Baptism -- Reproducing the divine light -- The ambrosian tradition -- Peter chrysologus and Baptism in fifth-century Ravenna -- The orthodox Baptistery in Ravenna -- The iconography -- The Cupola's central scene -- The ... xopó of the Apostles -- The thrones and altars register -- The level of the windows and of the Stucco Prophets -- The floor level -- Conclusion : encountering the divine in fifth-century Ravenna -- The Archbishops' Chapel in Ravenna -- Ravenna at the beginning of the sixth century -- The Chapel and the orthodox Baptistery -- The Architecture -- The inscription -- The iconography -- The light -- Conclusion -- Light in the context of the Eucharistie liturgy -- Ps.-Dionysius the areopagite -- San vitale in Ravenna -- Juliana Anicia and "Justinianic" churches -- Sixth-century Ravenna and the Church of San Vitale -- Venantius fortunatus and the Ravennate experience -- The architecture -- The orientation and openings -- The decoration -- The textures and colours -- Metal paraphernalia and artificial lights -- The figurative decoration -- The liturgy -- The new ritual mise-en-scène on the adriatic shores -- Conclusion -- Conclusion -- Excursus : the tempietto longobardo in Cividale -- Between east and west -- The tempietto -- The use and meaning of light -- Manipulating theophany on the eve of the carolingian renaissance -- Bibliography -- Index of persons -- Index of places.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Paulinus, -- of Nola, Saint, -- approximately 353-431.; Paulinus, -- of Nola, Saint, -- approximately 353-431; Licht, ...; Wat, Aleksander, -- 1900-1967.; Watowa, Ola, -- 1903-1991 -- Entretiens; Worship -- History -- Early church, ca. 30-600.; Liturgies, Early Christian; Baptism -- History -- Early church, ca. 30-600.; Liturgy and architecture; Light in architecture; Architecture -- Italy -- Ravenna; Light -- Religious aspects -- Christianity; Ravenna (Italy) -- Church history; Cultes -- Histoire -- ca 30-600 (Église primitive); Liturgie chrétienne primitive; Baptême -- Histoire -- ca 30-600 (Église primitive); Liturgie et architecture; Lumière en architecture; Architecture -- Italie -- Ravenne; RELIGION -- Christian Rituals & Practice -- Worship & Liturgy; RELIGION -- Institutions & Organizations; Architecture; Baptism -- Early church; Light in architecture; Light -- Religious aspects -- Christianity; Liturgies, Early Christian; Liturgy and architecture; Worship -- Early church; Italy -- Ravenna; Frühchristentum; Kirchenbau; Liturgie; Symbolik; Venetien; Art -- Aspect social -- Hongrie -- 1870-1914 -- Catalogues d'exposition.; Art -- Hongrie -- 1870-1914 -- Catalogues d'exposition.; Marché du travail -- France -- Franche-Comté (France) -- Statistiques; Migrations alternantes -- France -- Franche-Comté (France); 30-600; Church history; History